Evaluation of Mineral Trioxide Aggregate for Root end Closure of Nonvital Permanent Teeth with Open Apices (Update Dental College Journal, 2014)
Objective: To evaluate the clinical and radiological outcome of MTA in nonvital teeth with open apices. Methods: Twenty-five non-vital teeth with open apices were treated with MTA apexification procedure. Standard endodontic procedures were followed and an apical plug of at least 5 mm was created by using MTA after a calcium hydroxide intra-canal dressing for at least 1 week. Final obturation was done after 24 hours by vertical compaction technique using gutta percha. Patients were recalled at 3, 6, 9 and 12 months interval. Clinical outcome was evaluated by assessing pain, tenderness, mobility and sinus tract. Blind to the treatment record, two examiners assessed the pre-treatment and post-treatment radiographs. Each radiograph was scored with the Periapical Index (PAI) and the size of the apical lesion was measured. The presence of an apical bridge over MTA was also noted. Results: Clinically 92% success rate was found whereas radiologically absolute success rate was 84%. Before treatment the mean PAI was 3.6 and mean size of the lesion was 3.24 mm. But, after 12 months follow up, the mean PAI was 1.36 and the mean lesion size was 0.68 mm. An apical barrier over MTA was distinguishable in 5 cases. Conclusion: Apexification using MTA can be considered as a predictable treatment option than calcium hydroxide apexification. DOI: http://dx.doi.org/10.3329/updcj.v3i2.17994 Update Dent. Coll. j: 2013; 3 (2): 13-19